Perancangan Proyek Restoran Mellaca Eatery dengan Pendalaman Sense of Place - Lukito, Vieri Imanuel; rahadiyanti, melania (Universitas Ciputra Surabaya, 2022)
Mellaca Eatery is a restaurant with a Malaysian specialty located in Malang. In this project, the owner wants a refresh and a new concept for the restaurant that will be built in Jl. Bukit Dieng Permai. The owner wants this new restaurant to reflect more about “Kota Melaka” but on the other hand it can still maintain the DNA of the old restaurant that was dominated by an Industrial Style. Therefore, in this project the Sense of Place design approach is the ideal approach. In the Sense of Place approach, the atmosphere in the restaurant can be formed from the images, forms, and activities. The design style applied as the main image / theme for this restaurant is a combination of Industrial and Peranakan Style which is authentic in Malaysia. This main theme is shown through the use of materials, furniture, color palette, and accessories in the interior spaces. Meanwhile from an architectural perspective, the effort made is to combine various types of Historicism Building and Elements such as the famous Christ Church in Melaka, the Shophouses, and the ambience of Jonker Street to give the impression of Sense of Place on the shape of the building. In this project, the building is also designed to encourage activities such as a demonstration area for “Roti Canai” & “The Tarik” and many instagrammable spots filled with murasl depicting the sense of place of “Kota Melaka”. Through a combination of images, forms and activities, a Sense of Place will be formed in Mellaca Eatery.